Climate Communication on Improvement of Group Capacity - Eni Kardi Wiyati; Amiruddin Saleh; Sarwititi Sarwoprasodjo; Aida Vitayala S Hubeis (Institut Pertanian Bogor, 2014)
Group is one of medium used by the change agents to improve farmers' knowledge. The Ministry of Agriculture through the Bureau of Human Resources Extension outreach groups to improve the welfare state of the poor in the province of Central Sulawesi. One of the efforts made to increase the capacity of the group to provide guidance to the group. Group formed tailored to the type of commodity that is owned by the community. The existence of the group is influenced by many factors, one of which is climate of group communication. Diff erences in the degree of group climate, is influenced by how the group reach a level of reaction that members of the group create process of communication, participation raises the warmth and friendship, mutual trust, mutually acceptable, so that each member feels recognized and seriously satisfied to be in the group. The purpose of this study is to identify and analyze the group communication atmosphere in conjunction with effort to empower the group capacity. The Population are group members of READ (KR) in Poso District in Central Sulawesi Province. The study was designed using survey research is description.Keywords: Group Characteristics, Climate Communication and Capacity Improvement Building Group